Un dispositivo de experimentación para los evaluadores de validación de experiencias adquiridas - Sandrine Cortessis (Universidade do Porto, 2014)
In this article, we present a VAE tool (also RPL - Recognition of Prior Learning) which allows its appraisers to develop specific assessment skills from one year to the next with the support of a stabilized collective history. With the goal of training teachers in their new tasks as VAE assessors, the designers of the process contemplated places for dialog and regulation which favor the collective analysis of the VAE appraisal. Starting from the re-transcription of these collective debates, we observe how jury members analyze their new work experience and its challenges. We observed that the dialog between appraisers allows them to identify and stabilize a series of dilemmas and become aware of the variables leading them to their final decision. Regulation sessions become a place of resources and creativity, sustained both by expert and beginner appraisers.